Screening of Antioxidant, Antimicrobial and Phytochemicals Composition of Various Plant Parts of Cichorium Intybus: Pharmaceutical Science-Botany for better natural therapy - Maitry Choudhary; Priyanka Rajput; R.A. Sharma (International Journal of Life Science and Pharma Research, 2022)
The present study was conducted to evaluate the antioxidant and antimicrobial potential as well as the phytochemical composition of root, seed and leaves of Cichoriumintybus. The antioxidant activity was analyzed by detecting the 2, 2-Diphenyl-1- picrylhydrazyl DPPH radical scavenging potent of the constituents found in various plant parts of Cichorium intybus,whereas for analyzing in-vitro antimicrobial activity, agar well diffusion method has been opted. The antimicrobial activity of plant was tested against both pathogenic as well as non-pathogenic species of bacteria by analyzing the corresponding inhibition zone exhibited by various extracts of plant parts against the bacterial growth. Apart from this, the present study also involves the quantitative phytochemical evaluation of total ascorbic acid in root, seed and leaves of Cichoriumintybus. The antioxidant potential of the plant was found to be comparatively lower in seed and leaves of plant than in root in accordance to the determined IC50 value . From the antimicrobial activity analysis, it was concluded that majority of times the non-polar extracts of all plant parts were found to be more effective in inhibiting growth of bacteria. Most significant activity has been exhibited against gram negative bacteria Pseudomonas aeruginosa. The ascorbic acid content in plant was found in the range of 2.253±0.867 to 12.594±2.05µg/ml. From the results of the conducted research, the importance of plant as an antimicrobial and anti-oxidative agent has been established. So, the plant can further be introduced as a potential drug for herbal medicine in the treatment of human disorders.